Anatomical characterization of the inguinal lymph nodes using microcomputed tomography to inform radical inguinal lymph node dissections in penile cancer. Issue 8 (10th September 2020) - Marshall, Kaitlin; Nair, Shiva M.; Willmore, Katherine E.; Beveridge, Tyler S.; Power, Nicholas E.
Abstract: Background & Objectives: Radical inguinal lymph node dissections (rILND) for penile cancer risk significant postoperative lymphocele and lymphedema. However, reducing the risk of lymphatic complications is limited by our understanding of lymphatic anatomy. Therefore, this study aims to elucidate the lymphatic anatomy within the current surgical borders of a rILND. Methods: To visualize the position of the lymph nodes, tissue packets excised from the inguinal region of five fresh, male cadavers were imaged using microcomputed tomography (µCT). To standardize the position, rotation and size between specimens, each lymph node packet was aligned using a Generalized Procrustes analysis. Results: There was a median of 13.5 lymph nodes (range = 8‐18) per packet, with the majority (99%) clustered within a 6 cm radius of the saphenofemoral junction; a region 39%‐41% smaller than current surgical borders. No difference existed between the number of nodes between sides, or distribution around the saphenofemoral junction. Conclusions: This study provides the first 3D, in situ, standardized characterization of lymph node anatomy in the inguinal region using µCT. By using knowledge of the normal lymphatic anatomy, this study can help inform the reduction in borders of rILND to limit disruption and ensure a complete lymphadenectomy.